Genome-Wide Identification and Characterization of WRKY Gene Family in Peanut - Song, Hui; Wang, Pengfei; Lin, Jer-Young; Zhao, Chuanzhi; Bi, Yuping; Wang, Xingjun (Frontiers in Plant Science, 2016)
WRKY, an important transcription factor family, is widely distributed in the plant kingdom. Many reports focused on analysis of phylogenetic relationship and biological function of WRKY protein at the whole genome level in different plant species. However, little is known about WRKY proteins in the genome of Arachis species and their response to salicylic acid (SA) and jasmonic acid (JA) treatment. In this study, we identified 77 and 75 WRKY proteins from the two wild ancestral diploid genomes of cultivated tetraploid peanut, Arachis duranensis and Arachis ipaënsis, using bioinformatics approaches. Most peanut WRKY coding genes were located on A. duranensis chromosome A6 and A. ipaënsis chromosome B3, while the least number of WRKY genes was found in chromosome 9. The WRKY orthologous gene pairs in A. duranensis and A. ipaënsis chromosomes were highly syntenic. Our analysis indicated that segmental duplication events played a major role in AdWRKY and AiWRKY genes, and strong purifying selection was observed in gene duplication pairs. Furthermore, we translate the knowledge gained from the genome-wide analysis result of wild ancestral peanut to cultivated peanut to reveal that gene activities of specific cultivated peanut WRKY gene were changed due to SA and JA treatment. Peanut WRKY7, 8 and 13 genes were down-regulated, whereas WRKY1 and 12 genes were up-regulated with SA and JA treatment. These results could provide valuable information for peanut improvement.